Determinan Finansial dan Nonfinansial Corporate Social Responsibility Disclosure - Wiyarna, I Nyoman Adi; Sudana, I Putu (E-Jurnal Akuntansi, 2019)
This research was conducted at mining companies listed on the Indonesia Stock Exchange in 2013-2017. The sample in this study was determined by nonprobability sampling method with purposive sampling technique, and the samples obtained in this study amounted to 13 companies with 65 observations. The data analysis technique used in this study is multiple regression analysis techniques. The results of this study indicated that the variables of profitability, leverage, managerial ownership, firm’s growth and media exposure have a positive effect on disclosure of Corporate Social Responsibility. This shows that there is an exposure on high profitability companies, high-leveraged companies, high firm’s growth companies, large managerial ownership and high media pressure so that it can be understood that the company will disclose more detailed informtion about Corporate Social Responsibility to reduce the pressure. Keywords : Profitability; Leverage; Mnagerial Ownership; Firm’s Growth; Media Exposure;  CSR.